REALITAS IMPLEMENTASI SISTEM INFORMASI AKUNTANSI PADA UMKM: STUDI KASUS INDUSTRI KOPI CV TRI ANOM AGROTEKTUR (KADATUAN KOFFIE) - Wibowo, Muhammad Rafli; Rahmawati, Apriana; Pragama, Tegar Ditya; Wibowo, Sugiharto Hadi (AKUNTANSI DEWANTARA, 2025)
This research examines the digital transformation process of accounting information systems in SMEs within the coffee industry sector, focusing on a case study of CV Tri Anom Agrotektur (Kadatuan Koffie). Through a qualitative approach, the research explores the dynamics of information technology implementation, challenges in adopting digital accounting systems, and gaps between accounting standards and field practices. The findings reveal that while the company has attempted to adopt various digital platforms, significant challenges exist in system integration, internal control, and human resource capacity development. The study highlights the importance of a strategic approach to digital transformation, process standardization, and strengthening control systems to support sustainable growth. This research contributes to understanding SMEs' digital transformation and provides practical recommendations for developing effective accounting information systems.